Annual digest of human rights judgements 2006 - "Antony, M. J" (New Delhi, 2007)
This year's collection of judgements from the Supreme Court and the high courts relating to human rights violations has a positive starting point. In the past years, the Annual Digests started with dismal stories of custody deaths, disappearances and police atrocities. The courts merely lamented the situation and at best awarded compensation to widows or parents of the victims. This year, the volume starts with two path-breaking judgements of the Supreme Court which attempt to remedy the situation. The Supreme Court said in the first judgement that it has waited long enough for the executive and the law-makers to reform the police system and replace the century-old Police Act with a modern one. Stating that the court would now launch the reforms on its own, the judges passed a set of directions which are digested in the following pages. The second judgement dealt with the training and orientation of the police force.
Keywords: Human rights-judgements-2006